Tinjauan Kualitas Sistem, Kualitas Informasi dan Kualitas Layanan Pendaftaran Rawat Jalan dari Perspektif Admisi di Puskesmas Guntung Manggis - KHAIRUN NISA; Ni Wayan Kurnia Widya Wati (Jurnal Kesehatan Indonesia, 2023)
The quality of services based on outpatient registration applications has been implemented by the Guntung Manggis Health Center since 2019 and this is a technological innovation developed to facilitate health services. However, it’s known that the number of outpatient visits that have decreased in 2021-2022 is ? 47 visitors or ? 30-39%. So that Guntung Manggis Public Health Center patient satisfaction with service quality has regressed from the target (80%) which is 78.53%. The purpose of this study is to find out more in-depth about the quality of the information quality system and the quality of outpatient registration services from the perspective of admissions at the Guntung Manggis Health Center. This research’s a descriptive research with a qualitative approach. The number of samples is 6 people consisting of the Head of Record Medical and Outpatient Admissions Staff. The results of the study are the quality of the outpatient registration system from an admissions perspective including the category of "Good System Quality" at the Guntung Manggis Health Center, the quality of outpatient registration information from an admissions perspective including the category of "Good Information Quality" at the Guntung Manggis Health Center and the Quality of outpatient registration services from an admissions perspective including the category of "Good Service Quality" at the Guntung Manggis Health Center. In conclusion, the quality of the system, the quality of information and the quality of outpatient registration services from the perspective of admissions have been well fulfilled at the Guntung Manggis Health Center.